2020
DOI: 10.1103/physreve.101.022223
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of sensitivities of time-average quantities in chaotic systems

Abstract: We consider time-average quantities of chaotic systems and their sensitivity to system parameters. When the parameters are random variables with a prescribed probability density function, the sensitivities are also random. The central aim of the paper is to study and quantify the uncertainty of the sensitivities; this is useful to know in robust design applications. To this end, we couple the nonintrusive polynomial chaos expansion (PCE) with the multiple shooting shadowing (MSS) method, and apply the coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
(110 reference statements)
2
12
0
Order By: Relevance
“…A comparison with finite difference (FD) data is also presented. For dJ1 dc , there is a small bias, which has also been observed in the time-domain formulation of the method [19,20,42]; for dJ2 dc the matching with FD is very good.…”
Section: Application To the Kuramoto-sivashinsky Equationsupporting
confidence: 52%
See 1 more Smart Citation
“…A comparison with finite difference (FD) data is also presented. For dJ1 dc , there is a small bias, which has also been observed in the time-domain formulation of the method [19,20,42]; for dJ2 dc the matching with FD is very good.…”
Section: Application To the Kuramoto-sivashinsky Equationsupporting
confidence: 52%
“…Variants of the original LSS method include the Multiple Shooting Shadowing (MSS) [18,19,20] and the non-intrusive Least Squares Shadowing (NILSS), [21,22]. Both methods can be applied to large systems, but their computational cost scales with the number of PLEs.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the latter, i.e., UQ of sensitivities, is important in robust design applications, where the expectation of a QoI is minimized under uncertainty. The present work follows on from previous work of the authors in this area [23].…”
Section: Introductionmentioning
confidence: 97%
“…Evaluating a polynomial representation requires much less computational resources compared to the evaluation of an actual model, which makes the sampling of the parameter space far less computationally expensive [11]. When PCE is used to quantify uncertainty in a smooth system with finite variance, it provides exponential convergence at relatively low computational costs [12], and therefore PCE is the most commonly used UQ propagation technique when dealing with smooth processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in authors attempting to make PCE resistant to chaos, nonlinearity and the resulting nonsmoothness. To this end, Kantarakias et al [13] coupled PCE with the multiple shooting shadowing [23] method and applied it to two standard chaotic systems, the Lorenz system and the Kuramoto-Sivashinsky equation. It was found that at the quadrature integration points of PCE, the resulting regularization lead to accurate results that matched well with the Monte Carlo simulations at significantly lower computational costs.…”
Section: Introductionmentioning
confidence: 99%